Pengaruh Debt to Asset Ratio dan Total Asset Turnover Terhadap Return on Asset Perusahaan Makanan dan Minumam Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Nike Rachma Muzdalifah; Fitrawansyah Fitrawansyah; Yana Mustika (CV. ULIL ALBAB CORP, 2024)
The purpose of this study is to find out how the variables Debt to Asset Ratio and Total Asset Turnover affect Return On Asset both partially and simultaneously on Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The population in this study is 36 companies. The sampling method used was the purposive sampling method with a sample number of 9 companies. The hypothesis test uses statistical tests, namely partial tests (T test) and simultaneous tests (F test). The results of the hypothesis test partially show that the Debt to Asset Ratio has a significant negative effect on Return on Asset, and Total Asset Turnover has a significant positive effect on Return on Asset. The results of the hypothesis test simultaneously show that Debt to Asset Ratio and Total Asset Turnover have an effect on Return on Asset.